Pomen radiološke opredelitve naključno odkritih žariščnih sprememb ledvice - Rainer, Saša (Zdravniški vestnik, 2006)
Background Widespread routine use of cross-sectional imaging modalities (ultrasonography (US) and computed tomography (CT) leads to incidental discovery of many focal lesions in kidneys. It is important that these lesionsare correctly characterised since many of them represent maligrcancy. Incidentally discovered renal masses care often difficult to characterise because of their small size or complex morphology. Increasing numbers of renalcancers are discovered incidentally during imaging studies for other reasons, up to 40% of those masses are smaller than 3 cm. Together, US and CT are able to characterise up to 95% of renal masses larger than 15 mm. Bosniak classification proved to be very useful in distinguishing between benign and probably malignant cystic renal lesions. ln small solid focal lesions, evidence of tumoral vascularity is crucial, since many of them represent smallcancers. In CT, partial volume averaging can cause problems in detection of very small masses as well as their characterisation due to inacurate measurement of pre- and postcontrast density of the lesion. This can be overcome by using thin collimation and by modifying contrast administration protocols. Some hyperdense lesions are difficult to characterise because of sparse or non-opacification - they may represent hyperdense cystic mass or solid tumor (i. e. papillary renal cell carcinoma). US offers high-resolutiorcimaging of cystic and complex masses and non-invasive asessment of vascularity. Considering high sensitivity and specificity rates of US and CT, angiography has a very limited value in diagnosis of small, cystic or poorly vascularized renal masses. Conclusions How to manage patientswith incidentally discovered small renal tumor. Small tumors (<3 mm) rarely metastasize, are low grade and grow slowly. Therefore, in older or high-risk patients follow-up (watchful waiting) is an option. (Abstract truncated at 2000 characters)
Keywords: diagnostika; Kidney Neoplasms; Kidney, Cystic; Ledvica cistična; Ledvica, novotvorbe; ledvice; neoplasm; novotvorbe; Radiography; radiološka diagnostika; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; tumor; Ultrasonography